2019
DOI: 10.3324/haematol.2019.217448
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab-based regimens are highly effective and well tolerated in relapsed or refractory multiple myeloma regardless of patient age: subgroup analysis of the phase 3 CASTOR and POLLUX studies

Abstract: Daratumumab-based regimens are highly effective and well tolerated in relapsed or refractory multiple myeloma regardless of patient age: subgroup analysis of the phase 3 CASTOR and POLLUX studies.Phone: +34 923 29 1100 (250) Clinicaltrials.gov Identifiers: NCT02076009 and NCT02136134 together, this subgroup analysis of efficacy and safety of daratumumab was largely consistent with the overall populations.Trial registration: Clinicaltrials.gov identifiers: NCT02076009 and NCT02136134.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 29 publications
2
49
0
Order By: Relevance
“…Furthermore, inferior outcomes may also be associated with a lack of a more personalised regimen selection. For example, similar outcomes have been reported in the >75 years old patient cohort in both the POLLUX and CASTOR trials [10]. Treatment strategies for patients deemed TNE have evolved and it is clear that improvements in survival have been less impressive in this group of patients [7,11].…”
Section: Introduction-the Unmet Needmentioning
confidence: 55%
“…Furthermore, inferior outcomes may also be associated with a lack of a more personalised regimen selection. For example, similar outcomes have been reported in the >75 years old patient cohort in both the POLLUX and CASTOR trials [10]. Treatment strategies for patients deemed TNE have evolved and it is clear that improvements in survival have been less impressive in this group of patients [7,11].…”
Section: Introduction-the Unmet Needmentioning
confidence: 55%
“…Updated results of this trial after 19.4 months of median follow up revealed that the PFS benefit of DVd was most apparent in patients with a single prior line of therapy (median: not reached versus 7.9 months; P < 0.0001); a possible OS benefit was observed in this group of patients [26,27]. DVd was also superior to Vd in subgroups based on prior treatment exposure, lenalidomide-refractory status, time since last therapy, cytogenetic risk, or age [28]. At a median follow up of 40 months DVd, still prolonged PFS vs Vd in both patients with high (median 13.4 vs 7.2 months, P = 0.0002) and standard (median 18.4 vs 6.8 months P < 0.0001) cytogenetic risk [29].…”
Section: Daratumumab In Combination With Pismentioning
confidence: 88%
“…After a median follow up of 44.3 months DRd still prolonged PFS vs Rd in the intent-to-treat population (median 44.5 vs 17.5 months; HR, 0.44; 95% CI, 0.35-0.55; P < 0.0001), independently upon cytogenetic risk (high-risk: 26.8 vs 8.8 months, P = 0.01; standard risk: not reached vs 19.9 months, P < 0.0001), number of prior lines of therapy, different treatment-free intervals, and age [28,38]. Patients previously treated with lenalidomide or thalidomide and those refractory to bortezomib received similar benefits (all P < 0.01).…”
Section: Daratumumab In Combination With Imidsmentioning
confidence: 98%
“…The landscape of treatment options for relapse/refractory multiple myeloma (MM) continues to evolve dramatically. The advent of new generations of proteasome inhibitors (PI) [1,2], immunomodulatory drugs (IMiD) and now immunotherapies [3][4][5][6] has considerably improved survival. Unfortunately, however, these agents do not definitely eliminate MM cells and MM remains fundamentally an incurable disease.…”
Section: Introductionmentioning
confidence: 99%